The Brazil nut commodity chain in the Calha Norte region, State of Pará, Brazil - Krag, Márcia Nágem; de Santana, Antônio Cordeiro (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
The objective of this work was to analyze in a systematic way the Brazil nut commodity chain in the Calha Norte region, state of Pará. The primary data were obtained by means of structured questionnaires and interviews with the agents of the supply chain. For analysis of the results, a systemic approach was proposed using the ValueLinks methodology, with a view to the knowledge of the structure of the productive chain, analysis of comercial trade links and the systemic management of the supply chain. The results reaffirm that the extractive base remains the link where the smallest appropriation of value occurs. The agroindustry producers represent themselves as the central actors of the commodity chain and define the flow of the product during harvest, to determine the price. It is concluded there is deficiency in the productive chain vision between the links, which affects the performance of the arrangement and the possibility of local development with specialization in activities, however, there are local perspectives to strengthen the productive chain of Brazil nut in the Calha Norte region, to produce a product of biodiversity with strong commercial appeal (product of the Amazon). Therefore, it is essential to define and implement policies that promote the continuous improvement of the activities and processes in providing a positive impact for local and regional development.
Keywords: Non-timber forest products; Brazil nuts; Social actors; Marketing links; Systemic vision